Co-infection of blood borne viruses in blood donors: A cross-sectional study from North India. Issue 3 (June 2017) - Dara, Ravi C.; Tiwari, Aseem K.; Arora, Dinesh; Aggarwal, Geet; Rawat, Ganesh Singh; Sharma, Jyoti; Acharya, Devi Prasad; Bhardwaj, Gunjan
Abstract: Background: There are several studies on prevalence of individual infectious disease markers (mono-infection) in donors but none on prevalence of coinfection. Co-infection is significant as it leads to accelerated disease progression. We, therefore, evaluated the prevalence of co-infection among blood donors. Materials and methods: The cross-sectional analysis was conducted in blood donors. All donors were tested for anti-HIV I and II, HBsAg, anti-HBC IgM, anti-HCV, Malaria and syphilis by chemiluminescence and ID-NAT assay. All reactive donor samples were confirmed by using confirmatory assays. Donors were grouped as mono-infected and co-infected. The student t -test was used for comparison. Results: During the study period, a total of 106, 238 blood donors were tested. Mean age of donors was 34.2 years and 94.2% of blood donors were males. 1776 (1.67%) donor samples were confirmed serologically reactive. 1714 (1.61%) samples were reactive for single marker (mono-infected) while 62 (0.05%) donors' samples exhibited co-infection. 18 donors were positive for HBV+HCV followed by HIV +syphilis (14). Conclusion: We report for the first time the prevalence of different co-infection patterns in blood donors. Co-infection influence the disease progression; it would be important to investigate the co-infection prevalence in larger sample size.